‘Gel-Stacks’ gently confine or reversibly immobilize arrays of single DNA molecules for manipulation and study - Susana Calle-Casteñeda; Eamon Winden; Alejandro Vasquez-Echeverri; Matthew Schickling; Evelyn Browning; Juan Pablo Hernandez Ortiz; David C Schwartz (BioTechniques)
Large DNA molecules (>20 kb) are difficult analytes prone to breakage during serial manipulations and cannot be ‘rescued’ as full-length amplicons. Accordingly, to present, modify and analyze arrays of large, single DNA molecules, we created an easily realizable approach offering gentle confinement conditions or immobilization via spermidine condensation for controlled delivery of reagents that support live imaging by epifluorescence microscopy termed ‘Gel-Stacks.’ Molecules are locally confined between two hydrogel surfaces without covalent tethering to support time-lapse imaging and multistep workflows that accommodate large DNA molecules. With a thin polyacrylamide gel layer covalently bound to a glass surface as the base and swappable, reagent-infused, agarose slabs on top, DNA molecules are stably presented for imaging during reagent delivery by passive diffusion.